Enhancement of thermal robustness in magnetic tunnel junctions with perpendicular magnetic anisotropy - Law, Wai Cheung (2019)
Spin transfer torque magnetoresistive random access memory (STT-MRAM) has been recognized to be the most promising non-volatile memory technology for future technology nodes. STT-MRAM utilizes an array of magnetic tunnel junctions (MTJ) as its storage elements, which in its rudimentary form consists of two ferromagnetic electrodes sandwiching an insulating oxide. Ferromagnetic materials with perpendicular magnetic anisotropy (PMA) are found to offer higher thermal stability, excellent scalability and lower write current requirement as compared to ferromagnetic materials with in-plane anisotropy (IMA). However, the complexity behind creating materials with high PMA often means that compromises have to be made in order to satisfy all requirements simultaneously. Therefore, there remains a need to continue material research to ensure that STT-MRAM is compatible with the complementary metal-oxide-semiconductor backend-of-line (CMOS BEOL) processes. The objective of this thesis is to investigate different materials that are able to induce PMA while remaining relevant to contemporary MRAM applications. In this thesis, we focused on studying three different aspects within the MTJ stack that utilizes materials with PMA (denoted as pMTJ). In Chapter 3, Ho was observed to be a suitable candidate as a seed layer for Co/Pt multilayer as it can achieve hcp structure at 400°C annealing temperature appropriate for fcc-Co/Pt growth. In Chapter 4, amorphous Tb is used to replace Ta as an ultra-thin text-breaking coupling layer owing to its thermal robustness and strong exchange coupling. In Chapter 5, we studied how the limitation of Ta diffusion into the tunnel barrier can improve the thermal stability of the MTJ. Moreover, we observe that at elevated temperatures, the effective anisotropy field, Heff, decays at an increased rate as compared to saturation magnetization, Ms. This offers insight on the temperature dependence of thermal stability at standard MRAM operating conditions as well as optimization strategy beyond the 20nm technology node.